Groundwater lowering for construction of the Kilsby Tunnel, UK – pumping and tunnelling. Issue 4 (1st December 2021) - Chrimes, Mike; Preene, Martin
Abstract : The Kilsby Tunnel, constructed in the 1830s under the direction of Robert Stephenson, faced severe problems when a section of the tunnel, almost 400 m long, was driven through water-bearing unstable 'quicksand' conditions. Contemporary methods were not well suited to tunnelling through such conditions, and in previous decades, several canal tunnels had been planned to specifically divert around expected 'bad ground', and others took years to complete at great expense. Stephenson's team, drawing on their experience from the mining industry, did not take this approach and ultimately worked through the unstable ground, albeit with considerable delays and cost increases. This was achieved in part by establishing a large-scale groundwater pumping system, unique for the time, that lowered groundwater levels and stabilised the quicksand, which resulted from a buried channel of glaciofluvial sands, cut into bedrock, that had been missed by trial borings. Steam engines were used to pump from multiple shafts (including four dedicated pumping shafts, off set from the tunnel alignment), with a reported pumping rate of 136 l/s for several months. One unusual feature was the use of flatrod systems to transmit mechanical power horizontally; this allowed a single engine to drive pumps in several different shafts.